Designing Gamified Systems for Mental Health Support: An Exploratory Study - Prasetyaningrum, Putri Taqwa; Ibrahim, Norshahila; Yuniasanti, Reny; Setyaningsih, Putry Wahyu; Subagyo, Ibnu Rivansyah (Asosiasi Doktor Sistem Informasi Indonesia, 2024)
This exploratory study investigates the innovative design of gamified systems for mental health support, focusing on enhancing user engagement and well-being. By integrating user-centered design (UCD) principles with effective gamification elements, this research aims to develop engaging and therapeutically effective mental health interventions. Employing a mixed-methods approach, the study combines qualitative and quantitative data collection, including surveys, interviews, and user testing, to gather comprehensive insights from a diverse participant group. The findings reveal significant insights into user engagement, satisfaction, and the impact of gamification on mental health outcomes. While gamification enhances user engagement, balancing entertainment with therapeutic functionality is crucial. A comparative analysis between gamified and non-gamified app versions highlights the benefits and challenges of incorporating gamification in mental health contexts. The study concludes with practical recommendations for future research and design, emphasizing the need for continued innovation to optimize digital mental health interventions.